Low Molecular Weight Biobased Aromatics from Pyrolysis Liquids Using Zeolites: Yield Improvements by Using Pyrolysis Oil Fractions - Santosa, Dian S.; Rohrbach, Leon; Heeres, Hans; Venderbosch, Robbie H.; Heeres, Andre; Heeres, Hero J. (ACS omega, 2025)
Pyrolysis liquids from lignocellulosic biomass have the potential to be used as a feed for aromatics such as benzene, toluene, and xylenes (BTX) using catalytic upgrading with zeolites. We here report an experimental study on the conversion of various pyrolysis oil fractions to determine the most suitable one for BTX synthesis. For this purpose, the pyrolysis liquid was fractionated using several extraction/distillation steps to give four fractions with different chemical compositions. The fractions were analyzed in detail using nuclear magnetic resonance spectroscopy, elemental analysis, gas chromatography–mass spectroscopy, thermogravimetric analysis, Karl–Fischer titration, and gel permeation chromatography. Catalytic pyrolysis experiments were carried out using a tandem microreactor with H-ZSM-5 (23) as the catalyst. The highest BTX yield of 24% (on a carbon and dry basis) was obtained using the fractions enriched in phenolics, whereas all others gave far lower yields (4.4–9%, on a carbon and dry basis). Correlations were established between the chemical composition of the feed fraction and the BTX yield. These findings support the concept of a pyrolysis biorefinery, where the pyrolysis liquid is separated into well-defined fractions before further dedicated catalytic conversions to biobased chemicals and biofuels using tailored catalysts.